Application of Visual Design Principles and Motion Graphic in Re-Design Interactive Learning Video - Ady Purna Kurniawan; Sritenaya Geovani Putri; Agus Pratondo; Danica Rani Intani Putri (IJAIT (International Journal of Applied Information Technology), 2021)
E-learning-based learning has been widely applied in several educational institutions, one of which is Telkom University (Tel-U). Through the Center of e-Learning and Open Education (CeLOE) program established by Tel-U, network-based learning can be enjoyed by students. However, along the way, CeLOE encountered several obstacles, including the very rigid teaching materials that could have an impact on the reduced learning power of students. To solve this, it is necessary to improve the content of the material, especially learning videos by providing designs and animations for lecturer materials which on average contain full text. The approach used is the principle of visual design by utilizing motion graphics as the main aspect of material content with the ultimate goal of making learning videos more interesting and animated. Thus, the material presented can stimulate interest in learning for students at Telkom University.